Can the commodity futures be used as effective diversifiers for pension funds investment portfolios? A literature review - Eleftheriadis, Ioardanis; Anastasovitis, Ioannis (International Conference on Business and Economics - Hellenic Open University, 2023)
We examine from theoretical point of view whether commodity futures can produce diversification benefits for the pension funds’ investment portfolios. These asset tools have been classified in the alternative investments and as a result they are subjected to worldwide pension regulative restrictions. Reviewing the relative scientific literature of pension funds’ investment strategy and risk management, there is evidence that pension funds’ trustees might take advantage of commodity futures preference, mainly because of their a) returns’ low or negative correlation with these of other traditional options (bonds and stocks) and b) hedging positive properties against the inflation risk, resulting in the optimization of portfolios’ risk-return ratio. JEL Classifications: G23, Q02. Key words: Pension funds, Risk Diversification, Alternative Assets, Commodity Futures